Cultural Values and Decision to Work of Immigrant Women in Italy - Vincenzo Scoppa; Manuela Stranges (Institute for the Study of Labor (IZA), 2014)
We investigate the role of culture in explaining economic outcomes at individual level analyzing how cultural values from the home country affect the decision to work of immigrants in Italy, using the National Survey of Households with Immigrants. Following the epidemiological approach, we relate the probability of being employed in Italy for immigrant women with the female labor force participation (LFP) in their country of origin, taken as a proxy of cultural heritage and gender role model. Controlling for a number of individual and household characteristics, we show that participation in the labor market is affected both by the culture of females' and by their husband's origin countries. We also show that the relationship between own decisions in the host country and home country LFP cannot be attributed to human capital quality or discrimination and it turns out to be stronger for immigrants that maintained more intense ties with their origin countries. Finally, we investigate to what extent cultural influence is driven by religious beliefs: we find that religion is a key determinant of differences in female labor decisions, but, besides religion, other cultural values exert additional influence.
Keywords: Z10; Z13; J10; J15; J16; J20; 330; culture; immigration; labor force participation; epidemiological approach; gender; Italy